The princess diaries - Cabot, Meg (Macmillan Children's Books London, 2007)
What? A princess?? Me??? Yeah, right. Mia Thermopolis is pretty sure there's nothing worse than being a five-foot-nine, flat-chested freshman, who also happens to be flunking Algebra. Is she ever in for a surprise. First Mom announces that she's dating Mia's Algebra teacher. Then Dad has to go and reveal that he is the crown prince of Genovia. And guess who still doesn't have a date for the Cultural Diversity Dance?